CHANGE AND CONTINUITY OF THE TRADITIONAL JAVANESE LIFE STYLE OF ABDI DALEM HOUSES - Marchelia Gupita Sari; Dwita Hadi Rahmi (Journal of Architecture&ENVIRONMENT, 2017)
This  study  aims  to  understand  how  the  traditional  Javanese  life  styles  in  Abdi  dalem  houses  have  continued,  or transformed to adapt to modernization through the study of Abdi dalem  Houses located at three hamlets near the Imogiri Royal Mataram Islam Graveyard Complex,Yogyakarta. Abdi dalem  were not only the pioneer of the hamlet settlements, but also had considered as the priyayi who spread the Javanese culture to the village community. Focused on eighteen Abdi dalem  houses in Pajimatan,Giriloyo,and Banyusumurup, the measurements of the houses, interviews with the residents, and direct observations of residents’ daily activities are applied for the methodology of this study.The findings of this study are; First, most of the residents have inherited the houses from the previous generations. They tend to maintain the four sokoguru as main traditional structure and houses traditional orientation; Second, Abdi dalem  is still devout to be kawula for Kraton, so they are still avoiding any architectural elements which are resemblance to the royal graveyard architecture. Third, there are spatial function changes: the uses of sacred room changed to more profane function because of the space needs reason. The function of pendopo from social activities  changed to the house extension. Fourth, the spatial addition of the house in pawon and dalem adressed to fulfill the modern lifestyle.This study concludes that Abdi dalem  houses have maintained its traditional value in the aspect of the main structure, space, and kawula lan gusti obedience-life views. Pendopo and dalem has lost its initial function and meaning. Dalem and pawon are modified to adapt the modern life style.